(untitled) (Research, Society and Development, 2023)
The objective of this work was to build preparation technical sheets for preparations that serve the public with phenylketonuria. Eight preparations containing ingredients with reduced phenylalanine (PHE) content were researched and developed, which were: rice cake, cassava pie with spinach, baroa potato bread, passion fruit mousse, apple farofa, pineapple beijinho candy with sweet potato, potato pate and passion fruit trifles and collected information on Indicators of Edible Part and Conversion, yield, portion, cost and nutritional value, the latter with the aid of food composition tables. It could be observed that in most preparations there was a lower degree of waste during pre-preparation, except for the passion fruit mousse (Indicators of Edible Part=1.545). The recipes that gained and lost weight during the preparation process were, respectively, the passion fruit mousse and the pineapple beijinho candy with sweet potato (Indicator of Conversion=3.315 and 0.577). With regard to the phenylalanine content per serving, it ranged from 1.01 mg to 8.36 mg, corresponding to the preparations of passion fruit mousse and cassava pie with spinach. Thus, it was possible to prepare different recipes even with the restriction due to the PHE content found in various foods. The preparation technical sheets will assist in the control and preparation of meals for this public which have a very restrictive diet.